ULTRASOUND-GUIDED RECTUS SHEATH BLOCK ALONG WITH RIGHT SIDE SUBCOSTAL TRANSVERSE ABDOMINIS PLANE BLOCK VERSUS PORTSITE INFILTRATION WITH LOCAL ANESTHETICS IN LAPAROSCOPIC CHOLECYSTECTOMY FOR POST-OPERATIVE PAIN RELIEF: A COMPARATIVE STUDY - D MISHRA, RAJIV; PARIDA, MADHUSMITA; SWARO, SWASTIKA; SAMAL, SOUMYA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objectives: The objective of the study was to compare the efficacy between ultrasound guided rectus sheath block and the right side subcostal transverse abdominis plane with portsite infiltration with local anesthetics in laparoscopic cholecystectomy for post operative pain relief. Methods: Sixty patients posted for laparoscopic cholecystectomy were divided into two groups of 30 each. Group A received total dose of 80 mg (16 ml) of 0.5% ropivacaine 4 ml in each port and Group B received bilateral rectus sheath block with right-sided subcostal TAP block postoperatively, 80 mg (40 ml) of 0.2% ropivacaine was divided into two parts 20 ml in right-sided subcostal TAP and 20 ml in rectus sheath block, 10 ml in each side. Results: The first request of analgesia was significantly longer in combined block group than in the port site infiltration group (p=0.000). The numeric rating scale was reduced in patients given with abdominal field blocks when compared to patients obtaining port site infiltration. Mean NRS score was peak in pain score at the 6th h postoperatively in Group A and remained higher till 24 h in comparison Group B and was statistically significant. The overall tramadol consumption in Group A was approximately twice (215±51 mg) as compared to Group B (105±28 mg). Three cases of PONV were seen in Group A that is not statistically significant. The patient satisfaction score after 24 h was much higher with Group B in comparison to Group A (P 0.000). Conclusion: It is concluded that ultrasound-guided right-sided subcostal TAP and rectus sheath block produce effective post-operative analgesia for the incisional pain in laparoscopic cholecystectomy surgeries and act as a supplementary method in multimodal analgesia.